Maternal and neonatal outcomes in delivery with diagnosis of antepartum hemorrhage due to placenta previa at a tertiary hospital in Surabaya, Indonesia - Sarah Nia Amru; Indra Yuliati; Philia Setiawan (Majalah Obstetri & Ginekologi, 2022)
HIGHLIGHTS 1. To provide effective prevention and management of placenta previa, maternal and neonatal outcomes should be identified.2. Among mothers studied, no maternal mortality was found, but most newborns had prematurity and low birthweight.   ABSTRACT Objective: To identify maternal and neonatal outcomes in delivery with diagnosis of antepartum hemorrhage (APH) due to placenta previa. Materials and Methods: This was a descriptive retrospective study with cross-sectional design. Samples were taken using medical records with convenience sampling technique. Deliveries with history of APH due to placenta previa at Dr. Soetomo General Academic Hospital, Surabaya, Indonesia, on January 1 until December 31, 2019, were included. Results: In our study, 36 mothers were included. Maternal characteristics included age of 20–35 years in 72.2%, overweight in 50%, referral visits in 69.4%, from out of town (66.7%), bleeding onset at 3rd trimester (97.2%),  primigravida (8.3%), nulliparity (13.9%), 69.4% with history of C-section, and 83.3% no hospital readmissions. Maternal outcomes included 100% mothers diagnosed with complete placenta previa and performed C-section. The mothers were mostly (69.4%) diagnosed with placenta accreta spectrum (PAS). There were 36.1% hysterectomy, 33.3% postpartum hemorrhage, 50% blood transfusions, and zero maternal mortality. Neonatal outcomes included prematurity in 80%, low birth weight (LBW) in 51.5%, while 77.1% and 85.7% of newborns had no asphyxia at 1 and 5 minutes, consecutively. Conclusion: All mothers experienced complete placenta previa, and underwent C-section with most of the mothers were diagnosed with PAS. Less than half of them needed hysterectomy intervention because other patients with focal type PAS were planned for conservative surgery. Moreover, they mostly did not have postpartum hemorrhage with half of them needed blood transfusion. There was zero maternal mortality, with most newborns experienced prematurity, LBW but no significant asphyxia.